2016
DOI: 10.1111/ggi.12873
|View full text |Cite
|
Sign up to set email alerts
|

Development of an oral health‐related self‐efficacy scale for use with older adults

Abstract: We developed the GSEOH, with three factors and 20 items, and confirmed its reliability and validity. More studies are necessary to investigate the cross-cultural validity and reliability with larger samples from other countries. Geriatr Gerontol Int 2017; 17: 1406-1411.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…The instrument reliability was measured by the Alpha and Omega indexes, both indicating high levels of reliability. The Cronbach's Alpha obtained in this study was 0.95, identical to that found in the validation study of Jones et al 13 with Australian homeless people and very close to the value found in the study of Ohara et al 11 for the development of an oral health-related self-rated self-efficacy scale for use in Japanese older adults (0.924). Moreover this was higher than the value of 0.82 found in the study of Kakudate et.…”
Section: Stressedsupporting
confidence: 88%
“…The instrument reliability was measured by the Alpha and Omega indexes, both indicating high levels of reliability. The Cronbach's Alpha obtained in this study was 0.95, identical to that found in the validation study of Jones et al 13 with Australian homeless people and very close to the value found in the study of Ohara et al 11 for the development of an oral health-related self-rated self-efficacy scale for use in Japanese older adults (0.924). Moreover this was higher than the value of 0.82 found in the study of Kakudate et.…”
Section: Stressedsupporting
confidence: 88%
“…A reliable and valid twenty-item scale, developed by Ohara et al, (2016) [28] and used to evaluate self-efficacy in the context of oral health among older adults to measure three dimensions of personal beliefs about oral functioning (9 statements), oral hygiene habits (8 statements), and dental visit (3 statements). Older adults rate these statements on a four-point Likert scale (1 = not confident at all to 4 =very confident).…”
Section: Tool Iv: -Geriatric Self-efficacy Scale For Oral Health (Gseoh)mentioning
confidence: 99%
“…Fischbein’s integrative model (IM) of Behavioral Prediction integrates prior reason-based cognitive intervention models (Ajzen, 2002; Ajzen & Fishbein, 1980; Fishbein, 2008; Fishbein & Yzer, 2003; McCaul et al, 1988). It includes knowledge (Firmino et al, 2018), beliefs, self-efficacy (Ohara et al, 2017), and intentionality/planning/goal-setting (Lee, 2018; Newton & Asimakopoulou, 2015), variables that have been used to explain oral hygiene behaviors (McCaul et al, 1988; Tedesco, 1991; Tedesco et al, 1992). These factors, when built into interventions to improve self-care regimens, are shown to have short-term positive effects on cognitive domains and brushing/flossing and longer term improvements in clinical outcomes such as tooth decay, calculus, plaque, and bleeding (Ghaffari, Rakhshanderou, Ramezankhani, Buunk-Werkhoven, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%